Evaluation of targeted selective treatment strategy in sheep farm of Rajasthan - Singh, D; Swarnkar, C P (The Indian Journal of Animal Sciences, 2012)
The study was undertaken to develop and evaluate a colour chart to identify degree of anaemia in sheep of Rajasthan for management of haemonchosis and maintaining the anthelmintic susceptibility in population of parasites for longer period. Initially each sheep in a flock was monitored at monthly interval for correlating the intensity of Haemonchus contortus infection and blood profile (packed cell volume and haemoglobin). At each occasion photographs of conjunctivae were taken and a colour chart was developed (indicating 1–5 degree of conjunctiva colour) to indicate packed cell volume and anaemic status of the sheep. Based on the colour chart, the animals falling in category 1 to 3 were considered as normal while those falling in category 4 and 5 were considered as anaemic. The correlation between faecal egg count and degree of anaemia was positive in wormy season. The colour of conjunctiva was found to have negative correlation with haematological values. In subsequent years the colour chart was applied to all sheep flocks at Sheep Breeding Farm, Fatehpur (Rajasthan). It was observed that monthly proportion of sheep falling in category 4 or 5 were maximum of 17.35% in the month of September, 2008. The system was suitable in detecting the susceptible animals during wormy season. With this approach of targeted selective treatment (TST), the average frequency of anthelmintic drench in flock was 22.93±4.03% per annum compared to > 100% in conventional strategic treatment. In conclusion, though TST approach require some time and labour investment for selecting the animals for treatment but significantly reduced the cost of anthelmintic drenching as well as selection pressure for anthelmintic resistance.